The role of duration of dating on anxiety and commitment in early adulthood - Ulya, Rifqi; Pratama, Muhammad Fikri; Chusairi, Achmad (Jurnal Ilmiah Psikologi Terapan, 2023)
This study aims to investigate the role of the duration of dating on anxiety and commitment in early adulthood. The study involved 172 early adults (aged 20-30 years) who are currently in romantic relationships, selected using a purposive sampling technique. The research instruments included the anxiety scale and commitment scale, based on previous theoretical aspects. Data analysis was conducted using Two Way ANOVA with JAMOVI software to examine the role of the duration of dating on anxiety and commitment. The results of the study showed that there was no significant role of the duration of dating on anxiety and commitment. The study also examined the relationship between the duration of dating and several demographic variables such as gender, occupation, and long-distance relationship (LDR), but no significant effects were found. Therefore, it can be concluded that the duration of dating, whether long or short, does not play a role in the anxiety and commitment of couples in maintaining romantic relationships at a more serious level, such as marriage. The duration of dating was found to be unable to predict anxiety and commitment in relationships. Other variables related to dating, such as relationship quality, satisfaction, and personal factors, are considered to be more involved in predicting anxiety and commitment in dating relationships. This study has practical implications as a reference in premarital counseling and couples therapy to understand the dynamics of romantic dating relationships in individuals.